Semantic mediation modelling in the service component design. (21st March 2008) - Wu, Raymond
Semantic mediation is one of the big challenges in this century from scale and complexity. The main objective of mediation is to minimise the architecture gap, and reduce expenses. Achieving this objective requires multi-dimensional approaches including service strategy and integration. Therefore, architecture alignment and coherence are extremely important. We further extend our investigation by using AHP and eigenvalue techniques in component evaluation. Our proposal mainly argues that semantic mediation should not be initiated from the macro architecture; instead we propose that mediation should impact components first, to push semantics strategy directly into the micro process to be synthesised into the service layer.